Permanent tunneled catheter : Audit Analysis of Patients Presenting to A Tertiary Care Hospital. - Riaz, Muhammad Mohsin; Sabir, Shahzaib (Pakistan Journal of Kidney Diseases, 2024)
Vascular access for chronic kidney disease (CKD) patient is vital for a smooth transition from CKD 5 into hemodialysis (HD). Patient resist the idea of early creation of AVF till they manifest complications such as fluid overload, electrolyte or metabolic. This audit report is a review of our patients who had a permanent catheter placed for hemodialysis. Methods: Retrospective analysis of our patient registry data. Results: Majority of the patients had PC placed as permanent access for HD and only 40% of these were due to failure of an already pplaced vascular. Access. Conclusion: Majority of our patients had PC as the only solution left for HD and this may be due to delay in AVF creation. Fistula first policy should be implemented with the help of special CKD clinics and patient education.